2019
DOI: 10.1021/acsinfecdis.9b00196
|View full text |Cite
|
Sign up to set email alerts
|

High Enantiomeric Excess In-Loop Synthesis of d-[methyl-11C]Methionine for Use as a Diagnostic Positron Emission Tomography Radiotracer in Bacterial Infection

Abstract: Currently, there exists no accurate, noninvasive clinical imaging method to detect living bacteria in vivo. Our goal is to provide a positron emission tomography (PET) method to image infection by targeting bacteria-specific metabolism. Standard of care methodologies detect morphologic changes, image immunologic response to infection, or employ invasive tissue sampling with associated patient morbidity. These strategies, however, are not specific for living bacteria and are often inadequate to detect bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…For d ‐2‐ 18 F‐AF the highest radioactivity was retained for Proteus mirabilis , Salmonella typhimurium , Enterococcus faecalis and S. epidermidis (approximately 7‐8 Bq/10 million cells). The uptake levels of d ‐2‐ 18 F‐AF in these four bacteria were similar (<3‐fold difference based on incorporated radioactivity/10 million cells) to data recently obtained for d ‐[methyl‐ 11 C]methionine 33 . Evaluation of l ‐2‐ 18 F‐AF showed the highest uptake in K. pneumoniae , Acinetobacter baumannii , and M. marinum that retained between 3.5 and 4 Bq/10 million cells.…”
Section: Resultssupporting
confidence: 81%
“…For d ‐2‐ 18 F‐AF the highest radioactivity was retained for Proteus mirabilis , Salmonella typhimurium , Enterococcus faecalis and S. epidermidis (approximately 7‐8 Bq/10 million cells). The uptake levels of d ‐2‐ 18 F‐AF in these four bacteria were similar (<3‐fold difference based on incorporated radioactivity/10 million cells) to data recently obtained for d ‐[methyl‐ 11 C]methionine 33 . Evaluation of l ‐2‐ 18 F‐AF showed the highest uptake in K. pneumoniae , Acinetobacter baumannii , and M. marinum that retained between 3.5 and 4 Bq/10 million cells.…”
Section: Resultssupporting
confidence: 81%
“…One analog of D-methionine, D-[methyl-11 C]methionine, has been used to differentiate sterile inflammation from E. coli and S. aureus infections in a murine model, reporting an SUV max 8-10 times higher (SUV max = 0.8% ID/cc) in E.coli and S. aureus compared to [ 11 C]L-methionine (SUV max = 0.1% ID/cc) [146]. An in vitro study demonstrated the broad sensitivity of D-[methyl 11 C] methionine across a panel of clinically relevant DFI pathogens, including E. coli, P. aeruginosa, P. mirabilis, S. aureus, S. epidermidis, and E. faecalis, with the greatest uptake occurring in S. aureus and P. aeruginosa [147]. A recent study compared the uptake of D-5-[ 11 C]glutamine and L-5-[ 11 C]glutamine isomers in a murine dual pathogen myositis model with localized MRSA and E.coli infections.…”
Section: Emerging Radiotracers In Infection Imagingmentioning
confidence: 99%
“…A 2017 study has, however, demonstrated that both E. coli and S. aureus have high uptake of D-methionine, while the D-form has low uptake in animal and human tissue, for which reason D-[ 11 C]methionine in a mouse model was demonstrated to have much more infection-specific uptake than L-[ 11 C]methionine [ 53 ]. The group has since then developed a new synthesis for D-[ 11 C]methionine, performed in vitro tests showing uptake of the tracer in a broad range of clinically relevant bacteria, and are preparing for in-human evaluation of D-[ 11 C]methionine in patients with, e.g., vertebral discitis-osteomyelitis [ 54 ].…”
Section: Newer Tracers Considered For Bone Infection Imagingmentioning
confidence: 99%